UV-LED disinfection of emerging Vibrio pathogens: inactivation kinetics and reactivation potential - Romero-Martínez, Leonardo; Prieto-Pérez-Juez, Amalia; Nebot, Enrique; Moreno-Andrés, Javier (Frontiers in Marine Science, 2025)
IntroductionThe Vibrio genus includes aquatic bacteria from freshwater, estuarine, and marine environments, some of which pose significant risks to public and environmental health, highlighting the need for effective disinfection strategies. This study investigated the inactivation kinetics, reactivation potential, and energy efficiency of UV-LEDs emitting at 265 nm and 275 nm for controlling Vibrio alginolyticus and Vibrio parahaemolyticus, two emerging marine pathogens.MethodsBacteria were exposed to UV irradiation under different post-treatment conditions (0 d, 1 d-dark, 1 d-light), and both inactivation rate constants (k, mJ·cm-2) and electrical energy per n-log reduction (EEL,n) were obtained and analyzed.Results and discussionResults showed that V. parahaemolyticus was more UV-sensitive than V. alginolyticus, with inactivation rate constants of 1.22 and 1.60 cm2·mJ-1 at 265 and 275 nm, respectively, compared to 0.82 and 0.69 cm2·mJ-1 for V. alginolyticus. No significant differences were observed between the two wavelengths (265 nm and 275 nm) in terms of inactivation rate constants. As a result, achieving a 2-log reduction required lower fluences for V. parahaemolyticus (3.68–2.89 mJ·cm-2) than for V. alginolyticus (5.53–6.85 mJ·cm-2). Post-treatment incubation caused a decline in k-values one day after UV exposure, particularly under light conditions, with reductions of up to 59.9% at 275 nm and 48.8% at 265 nm. Although the decrease in k-values under dark conditions was less pronounced (average 27.9%), it remains noteworthy when compared with other fecal bacterial indicators. Electrical energy analyses revealed lower EEL,1 values at 275 nm, indicating greater energy efficiency, with values ranging from 0.012 to 0.050 kWh·m-3 for both Vibrio species. These results support the need for wavelength-specific optimization to balance disinfection efficacy and energy efficiency in marine water treatment and seafood safety applications.